Cosmos caudatus Leaf Extract Triggers Apoptosis of HSC-3 Cancer Cells by Decreasing Bcl-2 and Increasing Bax - Sandra, Ferry; Rizal, Muhammad Ihsan; Dhaniar, Afifah Yumna; Scania, Alifah Evi; Lee, Kyung Hoon (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Previous studies have demonstrated that Cosmos caudatus leaf extract (CCLE) exhibits cytotoxic effects against various types of human cancer. However, the CCLE cytotoxic effect towards oral squamous cell carcinoma (OSCC) cells has not been investigated. Therefore, this study was conducted to evaluate the effect of CCLE towards the viability and apoptosis in human oral squamous carcinoma (HSC)-3 cells.METHODS: HSC-3 cells were treated with various concentrations of CCLE for 24 h. The number of viable HSC-3 cells were measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), meanwhile the apoptotic HSC-3 cells were measured using sub-G1 assay. Mitochondrial membrane potential was measured using flow cytometry. Bcl-2 and Bax protein content of HSC-3 cells were measured using enzyme-linked immunosorbent assay (ELISA).RESULTS: CCLE treatment could decrease the number of HSC-3 viable cells and increase the percentage of HSC-3 apoptotic cells in concentration-dependent manner. In mitochondrial membrane potential assay, CCLE-treated group displayed a peak shifment from 104 to 103. Bcl-2 protein contents of CCLE-treated group were decrease in concentration-dependent manner, meanwhile Bax protein contents of CCLE-treated group were increase in concentration-dependent manner.CONCLUSION: CCLE could trigger apoptosis in HSC-3 cells by decreasing Bcl-2 protein content and increasing Bax protein content in concentration-dependent manner, leading to intrinsic apoptotic pathway.KEYWORDS: Cosmos caudatus, HSC-3, apoptosis, mitochondrial membrane potential, Bcl-2, Bax